A first qualitative snapshot: cardiac surgery and recovery in 10 children in the Red Cross War Memorial Children's Hospital, Cape Town, South Africa (2011–2016). (23rd November 2017) - Vivian, Lauraine; Comitis, George; Naidu, Claudia; Hunter, Cynthia; Lawrenson, John
Abstract: This article describes our qualitative research on the follow-up of 10 children, 5 years into recovery after cardiac surgery. The research was driven by a multi-disciplinary team of medical anthropologists, cardiologists, and an intensive care specialist and was based at the Red Cross War Memorial Children's Hospital where they underwent surgeries. The research sought to answer two questions; first, could we successfully maintain contact with and follow up the children; the second – which will be answered in future papers – asked what life was like for them and their families during surgery and later recovery. The results are presented as a discussion on the themes that arose in our engagement and analysis and not as clinical evidence. These showed that elective surgery although significantly delayed was successful, and all children were followed up at their medical appointments. The researchers, however, were unable to establish follow-up with all families over the duration of the study. In the final round of interviews in the respondents' homes, of 10 children, we remained in contact with seven. The discussion argues that effective communication and access to these children was often compromised by their coming from the poorer communities in the Cape Town metropolitan region, making them even more vulnerable during their recovery periods.